COMBINATION OF CHICKEN FERTILIZER WITH RICE HUSK ON GROWTH AND RESULTS RED ON ALUVIAL SOIL - Aisyah, Siti (Jurnal Sains Pertanian Equator, 2019)
Alluvial soil has very low organic matter and N-total, so the use of chicken manure with rice husk is expected to improve the physical and chemical properties of the soil and increase the yield of shallots. The purpose of this study was to obtain the best combination of chicken manure with rice husk for growth and onion yield on alluvial soil. This research was carried out in Parit Bugis Village, Segedong District, Mempawah District with a duration of 3 months, from May 16 to August 14, 2018. The design used in this study was Completely Randomized Design (CRD) with 6 treatment levels. Each treatment was 4 replications and 3 sample plants. The total number of plants is 72 plants. The variables observed in this research were plant height (cm), number of leaves (strands), number of tubers (fruit), wet weight of tubers (g), and dry weight of tubers (g). In addition, observations of environmental conditions were also carried out which included temperature ( °C), humidity (%) and rainfall (mm). The results showed that various combinations of chicken manure with rice husk had a significant effect on the observed variables of plant height at 8 weeks and number of tillers, but were not significantly different from plant height 2, 4, 6 weeks, number of leaves in the 2nd week , 4, 6, 8, fresh weight of tubers per hill and dry weight of tubers per clump.Keywords: alluvial soil, chicken manure fertilizer, rice husk, shallot.